Corporate Social Responsibility and Its Implementation in Tourism Industry: A Comparative Study between Indonesia and Australia - Anak Agung Bagus Ngurah Agung Surya Putra; Renee Sarah White; Kadek Sarna (Faculty of law Udayana University, 2018)
The concept of Corporate Social Responsibility (CSR) has been widely spread to developing countries. Most scholars argue that the CSR will give economic benefit to the local communities surrounding the company. Indonesia and Australia have adopted the concept of CSR into some legislation and regulations. When the laws of CSR were implemented in the field of tourism, some companies thought that they do not have any legal obligation to implement it. In practice, local communities have used CSR to demand the tourism industries to provide any social, cultural and economic facilities. This article is aimed at providing an analysis regarding the legal framework of Indonesian and Australian laws and regulations concerning CSR, particularly in Tourism Sector. In addition, it is intended to analyze how the implementation of CSR in tourism may strengthen the local communities. It is a normative legal research that primarily scrutinizes written official law and regulations as well as relevant court decisions regarding the issue of CSR, company, and tourism. It can be concluded that both Indonesia and Australia have regulated the concept of CSR very well as stipulated in official law and regulations. Regarding the implementation, by revolving within the scope of sustainable development concept as well as a gradual increase of tourism industries participation in CSR, the well-being of the local community will surely be improved.